PEMBUATAN DAN PENGUJIAN KUAT TEKAN BATAKO DENGAN PENAMBAHAN LIMBAH TULANG IKAN - Syaifuddin, Syaifuddin (JFT: Jurnal Fisika dan Terapannya, 2018)
This study aims to determine the minerals contained in fish bones using X-Ray Diffraction (XRD) and to find out the values that are relevant to standard values. This study used a test sample in the form of a beam with a length of 30 cm, a width of 10 cm and a height of 15 cm with the composition of fish bone powder varied from 10%, 15%, 20%, 25% and 30%. Make batako with a mix of sand, semen, air and fish bone powder. Based on the results of testing each parameter parameter, analysis of fish mineral minerals using XRD. The yield of fish oil (CaO) content is 65%, zinc (ZnO) 11%, Iron (Fe2O3) 22%, and Cu4O3 2%. While the average value for each parameter in the composition of 10% to 15% is obtained by the compressive strength of 25.21 Kg / cm2 and 40.16 Kg / cm2 (according to the SNI 3-0349-1989 standard class category IV and class III level of solid concrete brick).Keywords: brick, compressive strength, fish bone